Multiscale understanding of tricalcium silicate hydration reactions - Cuesta-García, Ana María; Zea-Garcia, Jesus D.; Londono-Zuluaga, Diana; Gómez-de-la-Torre, María de los Ángeles; Santacruz-Cruz, María Isabel; Vallcorba, Oriol; Dapiaggi, Monica; Sanfélix, Susana G.; García-Aranda, Miguel Ángel (Nature Publishing Group, 2018)
Tricalcium silicate, the main constituent of Portland cement, hydrates to produce crystalline calcium hydroxide and calcium-silicate-hydrates (C-S-H) nanocrystalline gel. This hydration reaction is poorly understood at the nanoscale. The understanding of atomic arrangement in nanocrystalline phases is intrinsically complicated and this challenge is exacerbated by the presence of additional crystalline phase(s). Here, we use calorimetry and synchrotron X-ray powder diffraction to quantitatively follow tricalcium silicate hydration process: i) its dissolution, ii) portlandite crystallization and iii) C-S-H gel precipitation. Chiefly, synchrotron pair distribution function (PDF) allows to identify a defective clinotobermorite, Ca11Si9O28(OH)2.8.5H2O, as the nanocrystalline component of C-S-H. Furthermore, PDF analysis also indicates that C-S-H gel contains monolayer calcium hydroxide which is stretched as recently predicted by first principles calculations. These outcomes, plus additional laboratory characterization, yielded a multiscale picture for C-S-H nanocomposite gel which explains the observed densities and Ca/Si atomic ratios at the nano- and meso- scales.